2018
DOI: 10.29252/jcbr.2.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antibiotic Resistance and β- lactamase Production in Clinical Isolates from a Tertiary Care Hospital in Central India

Abstract: Introduction: Antimicrobial resistance in bacterial pathogens is associated with high morbidity and mortality. We aimed to evaluate antibiotic resistance and β-lactamase production in clinical isolates of a tertiary care hospital in Central India. Materials and Methods: Clinical isolates (n=6472 isolates) from patients with infection were identified using standard microbiological techniques. Antibiotic susceptibility testing was performed according to the CLSI guidelines using the Kirby-Bauer disc diffusion te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…In this survey, ESBL production was found in 28.26% (398/1408). In line with this result, some researchers reported the rate of ESBL production as 29% and 30.23% 31 , 32 . In contrast, an earlier study revealed that 11.75% of uropathogens were ESBL positive 33 which is lower than our result.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In this survey, ESBL production was found in 28.26% (398/1408). In line with this result, some researchers reported the rate of ESBL production as 29% and 30.23% 31 , 32 . In contrast, an earlier study revealed that 11.75% of uropathogens were ESBL positive 33 which is lower than our result.…”
Section: Discussionsupporting
confidence: 57%
“…Elsewhere, the researcher reported 55.4% for ESBL production rate which is larger than ours 34 . These differences may be due to geographical area, time, and the diagnostic technique used 32 .…”
Section: Discussionmentioning
confidence: 99%
“…A signicant change in proportion and number of isolation of multi drug resistant (MDR) pathogens has increased over last decade. Global organizations such as World Health Organization (WHO), Centre for Disease Control and Prevention (CDC), and European Centre for Disease Prevention and Control (ECDPC), consider MDR (4) isolates as a global threat to public health worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…The MDR isolates are associated with increased morbidity and mortality, such agents usually fails to respond to conventional treatment so become more (5) tedious. So although rational use of antibiotics is necessary, development of new antimicrobial agent is in (4) pipeline.…”
Section: Introductionmentioning
confidence: 99%